DRUG AND SUBSTANCE ABUSE PROBLEM BY THE ZIMBABWEAN YOUTH: A PSYCHOLOGICAL PERSPECTIVE (Practitioner Research, 2020)
Drug abuse has become a problem among youths in Zimbabwe, so dire is the situation that more than half of the youths’ population, approximately 57% in Zimbabwe are involved in drug abuse. The statistics on youth drug abuse in Zimbabwe increase yearly despite measures implemented by various stakeholders to fight the pandemic. The study seeks to understand the problem of drug abuse within the Zimbabwean context from a psychological perspective. The current study takes a desk research approach to understand the problem of drug abuse by the youth in Zimbabwe. The study unearths the most affected age group by drug abuse, the causes of drug abuse, the types of drug abuse and the effects of drug abuse to that age group. The study reviewed relevant literature, using key terms in the study, which are youth, drug abuse and problem. Literature was systematically categorised into categories of causes of drug abuse, types of drug abuse and the effects of drug abuse among the youth. Findings from the study are that, the youth are the most affected age group by drug abuse in Zimbabwe and the problem stems from lack of self-control and negative self-concept on the youth drug abusers. The study also established that cannabis is the most abused drug in Zimbabwe and that the problem of drug abuse has negative effects to the drug abuser, family, community and nation at large. The current study recommends for future studies to establish intervention programs in Zimbabwe that aim to enhance self-control and self-concept in youth drug abusers.